Efforts To Improve Learning Outcomes Of Lower Service Through The Application Of Inquiry Learning Methods - Irfan; Achmad Karim; Cayati (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to improve the learning outcomes of volleyball underhand serve using the inquiry learning method for class IX students of SMAN 9 Gowa. This study is a Classroom Action Research (CAR) consisting of two cycles and each cycle consists of four meetings. This study took place at SMAN 9 Gowa. The subjects of this study were class IX students of SMAN 9 Gowa. The instruments in this study used test techniques, observation techniques and documentation techniques in the application of the volleyball underhand serve inquiry learning method. Based on the results of observations, discussions and research results, it can be concluded that learning volleyball underhand serve for class IX students of SMAN 9 Gowa for two cycles can improve student learning outcomes. This can be proven from the results of the study that the completion of learning outcomes based on KKM, in cycle I the percentage of graduation of class IX students of SMAN 9 Gowa was 56.66%, and increased in cycle II with a graduation percentage of 83.33%.